Implement a laboratory workshop in physics and electrotechnical disciplines in the face of COVID-19 pandemic - Viktor Shurygin; Alexander Deryagin; Lyubov Krasnova; Ilmir Sahabiev (Institute of Advanced Engineering and Science, 2022)
Studying physics and many related disciplines at all education levels includes not only learning the theoretical material, but also the formation of skills and abilities to apply the knowledge gained in practice. This occurs mainly during laboratory work when students directly contact with specific laboratory equipment. With the forced transition to distance learning due to the development of the COVID-19 pandemic, the main difficulties in many universities arose precisely during the implementation of laboratory workshops. This study analyzed the possibilities of modern digital teaching aids for the effective remote implementation of a laboratory workshop in physics and related disciplines. The study was carried out on the basis of the Elabuga Institute of the Kazan Federal University. There were 79 students took part in the experiment (second and third-year students). The results showed that a well-arranged combination of various digital tools and technologies makes it possible to effectively implement laboratory works in physics and electrotechnical disciplines in a distance learning format. The research results are useful for university teachers using distance learning technologies in laboratory work in natural science disciplines.